2019
DOI: 10.1155/2019/3120960
|View full text |Cite
|
Sign up to set email alerts
|

A Propensity-Score Matching Comparison between 27-Gauge and 25-Gauge Vitrectomy Systems for the Repair of Primary Rhegmatogenous Retinal Detachment

Abstract: Purpose To compare the anatomical and visual results and complications of 27-gauge versus 25-gauge transconjunctival sutureless vitrectomy for the management of primary rhegmatogenous retinal detachment. Methods A prospective, propensity score-matched 6-month study was performed. All patients underwent either 27-gauge or 25-gauge vitrectomy as the first surgical intervention and were followed up over a 6-month period, in order to evaluate anatomical success, change in best-corrected visual acuity (BCVA), and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 23 publications
(34 reference statements)
0
28
1
Order By: Relevance
“…Seven studies [ 15 , 21 24 , 26 , 31 ] were designed as prospective randomized/nonrandomized comparative study and four studies [ 17 , 25 , 29 , 30 ] were retrospective randomized/nonrandomized comparative study. Five trials [ 15 , 17 , 21 , 24 , 29 ] enrolled 554 eyes which were conducted on ERM and six studies [ 22 , 23 , 25 , 26 , 30 , 31 ] enrolled 386 eyes which were conducted on RRD. In total, 940 eyes were included in this meta-analysis; 439 eyes were assigned to the 27-G vitrectomy group and 501 eyes to the 25-G group.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven studies [ 15 , 21 24 , 26 , 31 ] were designed as prospective randomized/nonrandomized comparative study and four studies [ 17 , 25 , 29 , 30 ] were retrospective randomized/nonrandomized comparative study. Five trials [ 15 , 17 , 21 , 24 , 29 ] enrolled 554 eyes which were conducted on ERM and six studies [ 22 , 23 , 25 , 26 , 30 , 31 ] enrolled 386 eyes which were conducted on RRD. In total, 940 eyes were included in this meta-analysis; 439 eyes were assigned to the 27-G vitrectomy group and 501 eyes to the 25-G group.…”
Section: Resultsmentioning
confidence: 99%
“…First, in the RRD surgery, peripheral vitrectomy was more strenuous and complicated than in ERM surgery, and as a result, the operation time mostly depends on the proficiency of surgeon rather than the instrument gauges. Second, Veritti et al [ 26 ] reported that the 27-G probe has excellent fluidics procedures and high cut rate (7500 cpm) and it is very effective in shaving peripheral vitreous for RRD cases, so the operation time was not prolonged by smaller gauge in 27-G group. Third, although the qualities of included studies were adequate and the sensitive analysis minimized the heterogeneity as much as possible, the heterogeneity in the ERM subgroup may influence the final result.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations